Mini Library: Peningkatan Literasi Siswa SMP Plus AL-Amanah Bojonegoro - Kholidah, Neneng Rika Jazilatul; Mayasari, S.Pd.,M.Pd., Novi; Matin, Moh. Fuadul; Yudhianto, Haris Yudhianto; Hanifah, Lailatul (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2024)
ABSTRACTEducation is very important for humans, by obtaining good education humans will become cultured, dignified, and independent individuals. School is a place for students to receive formal education, but the education provided is not yet optimal especially in terms of student literacy, this is due to various reasons in each school. SMP Plus Al-Amanah School is a private school located in Dukuh Balongsumber, Sumbertlaseh, Bojonegoro Regency which has a library with an area of 135 m2 located in the eastern part of the school, but the book collection in the library is limited. In addition, the classrooms in the western part of the school have not been equipped with a library, so students in the western part have to walk around ± 200 meters to visit the library if they want to read a book. Community service has been carried out as an effort to increase students' interest in reading with the method of preparation, implementation, and evaluation. The result of this community service is to facilitate students whose classrooms are located in the western part to continue reading books during break time, and students will alternately fill the wall magazine with motivational sentences and clippings from newspapers. ABSTRAKPendidikan sangatlah penting bagi manusia, dengan mendapatkan pendidikan yang baik manusia akan menjadi manusia yang bermartabat, berbudaya serta mandiri. Sekolah merupakan wadah bagi siswa untuk mendapatkan pendidikan formal, namun pendidikan yang diselenggarakan belum cukup optimal khususnya pada literasi siswa, semua terjadi karena berbagai macam alasan yang ada di sekolah masing-masing. Sekolah SMP Plus Al-Amanah merupakan sekolah swasta yang beralamatkan di Dukuh Balongsumber Desa Sumbertlaseh Kecamatan Dander Kabupaten Bojonegoro yang memiliki perpustakaan cukup luas yaitu 135 m2 yang berlokasi di sekolah bagian Timur, selain itu buku yang tersedia di perpustakaan juga terbatas, sedangkan ruang kelas yang bagian barat belum memiliki perpustakaan sehingga siswa yang berada di sekolah bagian barat harus menempuh perjalanan sekitar eter untuk bisa mengunjungi perpustakaan jika hendak membaca buku. Pengabdian kepada masyarakat telah dilakukan sebagai upaya memotivasi minat membaca siswa dengan metode yang digunakan adalah persiapan, pelaksanaan dan evaluasi. Hasil pengabdian kepada masyarakat ini adalah mempermudah siswa yang ruang kelas sekolahnya berada di bagian barat untuk tetap bisa membaca buku di sela-sela jam istirahat serta siswa secara bergantian akan mengisi majalah dinding dengan kalimat motivasi dan kliping dari surat kabar.